Social movements for good: how companies and causes create viral change - Feldmann, Derrick, 1978- (Hoboken, New Jersey : John Wiley & Sons, 2016)
"Social Movements for Good tells the stories behind five of today's most successful Millennial-generation social good movements by companies and nonprofits. In exploring each movement highlighted in the book, the reader will learn about leaders that created these movements, individuals that responded, and the data and research behind the movement's success. The result is a full understanding of how social good movements are created today, how to truly activate a new generation, and the foundation and approach necessary to generate a public response to a social issue"--
Preface Acknowledgements About the Author Chapter One The Movement for Good Social Movements -- The Power of the People Chapter Two Empathy The Why Behind Social Movement Participation Viewpoint -- Social Movement Builder James Coan, University of Virginia Chapter Three From Belong to Owning a Movement How People Engage With Movements Today Viewpoint -- Social Movement Builder Adam Braun, Pencils of Promise Chapter Four Creating a Narrative to Believe In Social Movement Messaging Viewpoint -- Social Movement Builder Azita Ardanaki, Love Social Chapter Five Letting My Passion Be Heard Through a Sign Social Movement Symbolism Viewpoint -- Social Movement Builder Jay Coen Gilbert, B Lab and B Corporation Chapter Six The Business of Doing Good Companies and Social Movements Viewpoint -- Social Movement Builder Kim Jordan, New Belgium Brewing Brewing Company Chapter Seven Delivering Hope Abroad International Social Movements Viewpoint -- Social Movement Builder Shea and Raan Parton, Apolis Chapter Eight The Creative Behind a Movement Creative Approaches to Social Movements Viewpoint -- Social Movement Builder Joe Rospar, Blue State Digital Chapter Nine Using Leaders for Social Movements College Based Social Movements Viewpoint -- Social Movement Builder THON Volunteer Chapter Ten The Power of the Network Peer Engagement in Social Movements Viewpoint -- Social Movement Builder Scott Harrison, Charity Water Chapter Eleven # Hashtag Activism for Social Movements Viewpoint -- Social Movement Builder Mallory Brown, World Clothes Line Conclusion Notes Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Social movements; Leadership; Nonprofit organizations; Mouvements sociaux; Leadership; Associations sans but lucratif; social movements; nonprofit organizations; BUSINESS & ECONOMICS -- Nonprofit Organizations & Charities; Leadership; Nonprofit organizations; Social movements